Resistance of Pesanggaran Village Residents to the Release of Forest Areas for Land Redistribution Activities in Banyuwangi Regency - Fitra Alvian; M. Nazir Salim; Mujiati Mujiati (Sekolah Tinggi Pertanahan Nasional, 2026)
The Agrarian Reform policy in Indonesia aims to address land tenure inequality and alleviate poverty. This study examines the phenomenon of resistance among the residents of Pesanggaran Village, Banyuwangi Regency, to the Land Tenure Settlement Program for Forest Area Arrangement (PPTPKH), which was first implemented in Java. Using descriptive qualitative methods, data collection was conducted through observation, interviews, and document studies. The findings indicate that the main cause of resistance was community dissatisfaction because the forest area release policy only covered residential land (house sites) and did not accommodate their agricultural land. In addition, resistance was triggered by indications of local political interests, misunderstandings of information from Community Groups (Pokmas), and residents' concerns about land diversion for mining activities. Despite the resistance, the Agrarian Reform Task Force (GTRA) successfully resolved the conflict through a persuasive approach, allowing the land redistribution program to continue. Following the resistance, the implementation of land redistribution in Banyuwangi Regency recorded achievements as a national model in the use of electronic certificates. A total of 10,323 electronic certificates were issued, covering 470 plots of land in Pesanggaran Village. This success was supported by the political will of stakeholders, including the regional government's policy of exempting Land and Building Acquisition Tax (BPHTB) for program participants. This study concluded that active community participation and transparent communication were key to the successful acceleration of agrarian reform in forest areas.